Optimizing fly ash and rice husk ash as cement replacements on the mechani-cal characteristics of pervious concrete - Navaratnarajah Sathiparan; Daniel Niruban Subramaniam (Sustainable structures, 2025)
Replacing cement with fillers while being environment-friendly contributes to the performance enhancement of conventional concrete. In the investiga-tion, nine batches of concrete mix were prepared with different amounts of cement, fly ash (FA) and rice husk ash (RHA). This experiment investigated the consequence of substituting cement with FA at various water-to-binder (W/B) proportions. The FA content was ranged from 5% to 20% of cement by weight, and the W/B ratio was adjusted to 0.3, 0.35, 0.4, and 0.45. Further-more, for 10% cement replacement, FA and RHA combination of 10:0, 7.5:2.5, 5:5, 2.5:7.5 and 0:10 by weight were used. When FA alone was used as cement replacement, the optimal mix achieved a 28-day compressive strength of 31.33 MPa at a W/B ratio 0.40 with 10% FA. Moreover, incorpo-rating FA and RHA resulted in a cost reduction of approximately 15% per cubic meter of concrete and a decrease in CO₂ emissions by 20% compared to conventional concrete production. The findings demonstrate that FA and RHA can be effectively combined to manufacture pervious concrete that enhances performance, reduces costs, and minimizes environmental pollu-tants.